Human needs fulfillment: contributing factors of Eudaimonic Wellbeing - Abu Bakar, Aisyah; Mohamed Osman, Mariana (Malaysian Institute of Planners, 2022)
The Maslow hierarchy of needs and Eudaimonic Wellbeing (EWB), which falls under the Subjective Wellbeing (SWB) discipline, are the two concepts that are covered in the study. Issue: The hierarchy of needs does not require that people have to completely fulfil one need before moving up to the succeeding need. Recognizing human needs that are meaningful in promoting SWB, in this instance eudaimonia, is crucial to comprehending the hierarchy's relevance. Purpose: The purpose of this research is to look at the degree of EWB in connection to the difficulty and convenience of meeting human needs in Malaysia. Approach: Mann Whitney U-Tests were employed to determine the median of HF across the difficulty and convenience of meeting 24 human needs. These human needs are the essentials and living conditions for which people strive for. Findings: EWB is considerably increased by the convenience with which the majority of human needs can be met. The research also suggested that satisfying eight human needs for which EWB did not vary considerably was unlikely to impact EWB. These eight requirements were categorised by Maslow's Hierarchy of Needs as biological and physiological needs, safety and security needs, belonging and love needs, and self-actualization needs.